IoT-powered protection: the smart door access system - Zainuddin, Ahmad Anwar; Mohd Nor, Rizal; Amir Hussin, Amir 'Aatieff; Mohd Sazali, Muhammad Nurzikry; Mohd Razali, Muhammad Irfan Zaki; Khalid, Muhammad Nor Syahmi; Fazail, Muhammad Nazmi; Norazman, Nik Muhammad Faris Firdaus (Academica Press Solution, 2024)
The proliferation of Internet of Things (IoT) technology has catalysed innovations in home security systems, particularly in the realm of smart door access. This study proposes a robust and efficient IoT-enabled smart door lock system. Traditional physical key door locks are fraught with vulnerabilities, ranging from susceptibility to damage to the risk of unauthorized duplication. In response, this research introduces a novel IoT Smart Door Lock system designed to alleviate these concerns. Utilizing Wi-Fi connectivity and smartphone integration, the system provides keyless access control, rendering traditional keys obsolete. Through the incorporation of NodeMCU ESP 8266 microcontroller and Virtuino IoT application, users can securely unlock doors with their smartphones, bolstering both security and convenience. Furthermore, the HiveMQ MQTT broker is used to enable efficient machine-to-machine communication within the IoT component, improving the efficiency and interoperability of the system. The practical implementation and testing of the system demonstrated its efficacy, achieving a 100% success rate across all functions. Moreover, a trial deployment at the Centre of Excellence for Cybersecurity (CoExCys) office yielded positive results, underscoring its potential applicability in diverse environments. By leveraging IoT technology, this innovative smart door access system represents a significant advancement in home security, offering users a seamless and reliable solution to safeguard their premises while enhancing accessibility and peace of mind.